2015
DOI: 10.1002/fsn3.229
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimum oven cooking procedures for lean beef products

Abstract: In order to determine optimum oven cooking procedures for lean beef, the effects of searing at 232 or 260°C for 0, 10, 20 or 30 min, and roasting at 160 or 135°C on semimembranosus (SM) and longissimus lumborum (LL) muscles were evaluated. In addition, the optimum determined cooking method (oven‐seared for 10 min at 232°C and roasted at 135°C) was applied to SM roasts varying in weight from 0.5 to 2.5 kg. Mainly, SM muscles seared for 0 or 10 min at 232°C followed by roast at 135°C had lower cooking loss, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Specifically, center and mid portions of steaks cooked to 57°C IT had the greatest (P < 0.05) amount of these methyl esters compared with all other IT and layer combinations. As previously stated, thermal treatment tends to degrade ester bonds (Domínguez et al, 2014;Rodas-González et al, 2015;Biller et al, 2017).…”
Section: Internal Temperature × Layermentioning
confidence: 82%
“…Specifically, center and mid portions of steaks cooked to 57°C IT had the greatest (P < 0.05) amount of these methyl esters compared with all other IT and layer combinations. As previously stated, thermal treatment tends to degrade ester bonds (Domínguez et al, 2014;Rodas-González et al, 2015;Biller et al, 2017).…”
Section: Internal Temperature × Layermentioning
confidence: 82%
“…This result is probably related to the change of meat surface colour as a result of non‐enzymatic browning reactions such as caramelisation and Maillard due to sealing process. Similar results have been reported in many studies dealing with the effect of sealing on colour of meat (Rodas‐González et al ., 2015; Yoo et al ., 2020; Lee et al ., 2022). Indeed, the sealing process had a significant effect ( P < 0.01) on the outer surface colour of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Sealing is often applied as a preparatory step in various cooking methods (Labensky & Hause, 2007). Sealing can be applied in combination with moist heat cooking or low temperature dry heat cooking methods (Rodas‐González et al ., 2015). It has been reported that the sealing process plays an important role in reducing moisture loss and odour component (soluble protein and fat etc .)…”
Section: Introductionmentioning
confidence: 99%
“…Since same ingredients were used in preparing the burgers, except the meat or meat alternative sources, the difference in composition may be attributed to the meat sources. Raw lean beef was observed to contain 30.61% protein and 3.49% fat at 64.8% moisture which translates to 86.93% protein and 9.91% fat in dry weight basis [13]. In the same vein, lean chicken meat of the breast and thigh contained an average of 21.1% protein at 71.1% moisture content and this translates to 73.1% crude protein in dry weight basis [14].…”
Section: Discussionmentioning
confidence: 99%